1996
DOI: 10.1111/j.1365-2958.1996.tb02559.x
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus subtilis soj‐spo0J locus is required for a centromere‐like function involved in prespore chromosome partitioning

Abstract: During sporulation in Bacillus subtilis a small prespore cell is formed by an asymmetric cell division. Pre-spore chromosome partitioning occurs by a specialised mechanism in which septation precedes chromosome movement. We show that the spo0J gene is needed to specify the orientation of the chromosome at the time of polar division and to impose directionality on the subsequent transport of the remainder of the chromosome through the septum. Both phenotypes may arise by disruption of a centromere-like apparatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(162 citation statements)
references
References 31 publications
8
152
2
Order By: Relevance
“…Recently, important progress has been made in the understanding of the active chromosomal segregation process in vegetative and sporulating B. subtilis cells (Ireton et al, 1994;Sharpe and Errington, 1996;Glaser et al, 1997;Lin et al, 1997;Webb et al, 1997). It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, important progress has been made in the understanding of the active chromosomal segregation process in vegetative and sporulating B. subtilis cells (Ireton et al, 1994;Sharpe and Errington, 1996;Glaser et al, 1997;Lin et al, 1997;Webb et al, 1997). It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that 30% of the chromosome containing oriC has a centromere-like function that, during binary fission and sporulation, migrates actively towards the cell poles (Sharpe and Errington, 1996;Wu and Errington, 1994;Glaser et al, 1997;Webb et al, 1997). Because accurate segregation is affected in spoOJ mutant strains (Ireton et al, 1994;Sharpe and Errington, 1996), the SpoOJ protein was a prime candidate for being involved in the chromosomal segregation process. Using in vivo cross-linking techniques, the SpoOJ protein was recently shown to be associated with short DNA sequences containing the same DSE (Lin and Grossman, 1998) that is repeatedly present in the 29 genome.…”
Section: Discussionmentioning
confidence: 99%
“…Prespore-compartment-specific gene expression assays in B. subtilis show that spo0J mutants have defects in the orientation of the prespore chromosome (Sharpe & Errington 1996), suggesting that Spo0J is involved in the spatial organization of the origin proximal regions of the chromosome. However, Spo0J is not required for proper positioning or movement of the oriC region in B. subtilis during vegetative growth (Webb et al 1998).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
“…Furthermore, null mutants of ParB are lethal in Caulobacter crescentus (Mohl et al 2001), and mutations in spo0J in B. subtilis result in the formation of up to 3% anucleate cells (Ireton et al 1994). Spo0J/ParB mutants of B. subtilis and Pseudomonas aeruginosa are viable but display perceptible defects in chromosome segregation in both vegetative and sporulating cells (Godfrin-Estevenon et al 2002;Ireton et al 1994;Lewis et al 2002;Sharpe & Errington 1996). During vegetative growth, deletion of the parAB genes of Pseudomonas putida slightly increases the formation of anucleate cells, but during both the transition from exponential to stationary growth conditions and during overexpression of parAB, high levels of anucleate cells were formed (Godfrin-Estevenon et al 2002).…”
Section: Par Proteins Encoded By Bacterial Chromosomes-components Of mentioning
confidence: 99%
“…Another gene involved in DNA segregation in B. subtilis is spoOJ. SpoOJ is similar to the ParB family of plasmid-encoded partition proteins and is required for proper chromosome segregation during vegetative growth (13) and for correct chromosome positioning during sporulation (38). SpoOJ colocalizes with the origin region of the chromosome (9,20,22) and binds to specific sites located in the origin-proximal ϳ20% of the chromosome (21).…”
Section: Vol 182 2000mentioning
confidence: 99%